A Comparative Study of McKenzie Back Program and Conventional Physiotherapy in Relieving Backache due to Lumbar Disc Prolapse. (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To compare McKenzie back program and conventional physiotherapy in reducing pain and functional disability in patients with backache due to lumbar disc prolapse.Methods: This randomized controlled trial was conducted in Orthopedic Department Pir Abdul Qadir Jeelani Institute of Medical Sciences, Gambat Khairpur Sindh. The duration of this study extended from 2nd March 2019 to 2nd February 2021. All patients with backache due to lumbar disc prolapse fulfilling the inclusion criteria were randomly divided into two equal groups: Group A (McKenzie back program) and group B (Conventional physiotherapy). Pre-intervention pain assessment was done with Visual Analogue Scale (VAS), spine mobility with Fingertip-to-Floor distance (FTF) measured in centimeter and disability with Oswestry Disability Index (ODI) questionnaire in both groups and compared with post-intervention values at 4th, 6th and 8th week. P value was calculated with Chi-square test. P value< 0.05 was considered significant.Results: The total number of patients analyzed were 120.Both group A and B had 60 patients each. The mean age of group A patients was 46.4±5.3 years and group B 45.8±6.4 years. Male patients were 36 (60%) and female 24 (40%) in group A. In group B male patients were 33 (55%) and female 27 (45%). Statistically significant improvement was noted in FTF in group A at 2nd and 4th week (P < 0.05) post-intervention. At 8th week post-intervention VAS, FTF and ODI significantly improved in group A (P< 0.05) than in group B.Conclusion: McKenzie back program is more effective in reducing pain, increasing lumbar spine mobility and decreasing disability than conventional physiotherapy and stretching exercises in patients with backache due to lumbar disc prolapse.